The study of pea flour in the production of ‘Muruku’ / Nurul Azlin Tokiman - Tokiman, Nurul Azlin (2008)
The study of pea flour in the production of ‘muruku’ was conducted by incorporation of lentil flour and chickpea flour into two different formulations. The aims of this study were to produce a new, healthier ‘muruku’ using pea flour, to study the oil reduction in pea flour based ‘muruku’ compared with the commercial premix ‘muruku’ and to obtain the acceptability of the new ‘muruku’ through sensory evaluation. Four formulations of lentil flour and three formulations of chickpea flour based ‘muruku’ were developed and for control, the commercial premix ‘muruku’ flour was used with the addition of the same amount of salt and spices. All formulations have the same amount of glutinous rice flour. The amount of pea flour was highest in formulation 1 which was 80% and decreased 10% gradually from each formulation down to 60% in chickpea flour while 50% in lentil flour based ‘muruku’. Besides, the amount of rice flour is zero in formulation 1 and this amount increase 10% from each formulation up to 30% in lentil based ‘muruku’ and 20% in chickpea based ‘muruku’. Chemical analyses were carried out to determine uptake ratio and proximate composition for different fomulations of pea flour based ‘muruku’. Physical test were carried out to determine the texture (fracturability), and colour measurement. Meanwhile, two sensory evaluations were carried out which were QDA to obtain detailed description of ‘muruku’ characteristics in term of colour (brownish), crispiness, hardness, beany aftertaste, hotness, oiliness, and overall acceptability. Another sensory evaluation carried out to determine the acceptability of pea flour based ‘muruku’ in term of colour, taste, texture, and overall acceptability using hedonic scale. It was found that incorporation of pea flour in ‘muruku’ resulted in decreased of oil uptake compared to control which were in the range of 0.64 to 0.8 for lentil flour while 0.77 to 0.83 for chickpea flour. It was also found that fat, protein, fibre, and ash composition of ‘muruku’ increased with the incorporation of pea flour. Besides, the fracturability of ‘muruku’ reduced with the incorporation of pea flour compared to the control ‘muruku’. While, for sensory evaluation, results showed that all pea flour based ‘muruku’ formulations can be accepted by the panelists. However, the score for all attributes were not significantly different (p>0.05) since panelists were unable to detect the difference among each formulations.